1986
DOI: 10.1128/aac.29.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of ciprofloxacin, enoxacin, and ofloxacin in experimental Pseudomonas aeruginosa pneumonia

Abstract: The therapeutic activity of ciprofloxacin, enoxacin, and ofloxacin was evaluated in guinea pigs with acute and chronic experimental Pseudomonas aeruginosa pneumonia. Ciprofloxacin, enoxacin, and ofloxacin are three newly developed quinoline carboxylic acid derivatives with excellent in vitro activity against Pseudomonas aeruginosa (1,2,4,7,9,15,16,29,33). These compounds also offer interesting therapeutic alternatives for the treatment of P. aeruginosa infections because of their prolonged half-life and high t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
1

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…The benefit of adding azlocillin to ciprofloxacin therapy was particularly evident in studies using doses of ciprofloxacin that resulted in low ratios of the peak drug concentration to the MIC [23][24][25][26]; addition of azlocillin was associated with improved bacterial killing [23,24] or survival [25,26] or suppression of bacterial resistance to ciprofloxacin [23]. In contrast, other investigators concluded that adding an antipseudomonal penicillin to ciprofloxacin was not advantageous [27][28][29]. The discrepancies in outcome between different studies as well as those obtained in our model may stem from differences in initial bacterial inoculums used (critical to include drug-resistant subpopulations) [6,27], assessment only of early bactericidal effects [29], or dosage regimens that produced higher ciprofloxacin [28] or lower JS-lactam concentrations [27] in animals than those obtained in humans with usual doses.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefit of adding azlocillin to ciprofloxacin therapy was particularly evident in studies using doses of ciprofloxacin that resulted in low ratios of the peak drug concentration to the MIC [23][24][25][26]; addition of azlocillin was associated with improved bacterial killing [23,24] or survival [25,26] or suppression of bacterial resistance to ciprofloxacin [23]. In contrast, other investigators concluded that adding an antipseudomonal penicillin to ciprofloxacin was not advantageous [27][28][29]. The discrepancies in outcome between different studies as well as those obtained in our model may stem from differences in initial bacterial inoculums used (critical to include drug-resistant subpopulations) [6,27], assessment only of early bactericidal effects [29], or dosage regimens that produced higher ciprofloxacin [28] or lower JS-lactam concentrations [27] in animals than those obtained in humans with usual doses.…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Reduction in cfu/rnilliliter over 24 h was significantly greater for combination therapy using any dosing schedule against the two azlocillin-susceptible and the doubly resistant strains than that observed for single-drug therapies (P < .05); there were no differences between simultaneous and staggered regimens against the three strains (P > .05). For the strain with the highest MIC to ciprofloxacin (i.e., CRAs), simultaneous and staggered administration with azlocillin given first (i.e., C-O/ apy with a fluoroquinolone plus a JS-lactam [23][24][25][26][27][28][29]. The benefit of adding azlocillin to ciprofloxacin therapy was particularly evident in studies using doses of ciprofloxacin that resulted in low ratios of the peak drug concentration to the MIC [23][24][25][26]; addition of azlocillin was associated with improved bacterial killing [23,24] or survival [25,26] or suppression of bacterial resistance to ciprofloxacin [23].…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…The amount of known metabolites (demethyl and N-oxide compounds) excreted in urine reached only 4.3% (intravenously) and 4.0% (orally). Transient headaches in some volunteers were the only side effects registered.6-Fluoro-7-piperazino-4-quinolones are noteworthy both for the wide range and intensity of activities against gramnegative bacilli and cocci in vitro and the capacity to control experimentally induced systemic infections with selected bacteria when administered orally in well-tolerated doses (9,15,27).Ofloxacin {HOE 280, DL 8280; (±)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl) -7-oxo-7H-pyrido[1,2,3-de] [1,4]benzoxacine-6-carboxylic acid} is a new quinolone carboxylic acid derivative showing a broad antimicrobial spectrum against gram-positive and gram-negative bacteria (1,11,17,22,27). This substance was found to be more active than norfloxacin and pipemidic acid (22), its in vitro antibacterial activity being almost comparable to those of gentamicin, tobramycin, and newer cephalosporins (9,11,27).…”
mentioning
confidence: 99%
“…6-Fluoro-7-piperazino-4-quinolones are noteworthy both for the wide range and intensity of activities against gramnegative bacilli and cocci in vitro and the capacity to control experimentally induced systemic infections with selected bacteria when administered orally in well-tolerated doses (9,15,27).…”
mentioning
confidence: 99%
“…It has been demonstrated that several quinolone derivatives are useful in the treatment of P. aeruginosa pneumonia in normal and neutropenic guinea pigs (4,9,27). Sparfloxacin (AT-4140) is a newly developed quinolone for oral use that has broad and potent antibacterial activity (14).…”
mentioning
confidence: 99%